(untitled) (Journal of the College of Basic Education, 2024)
There were several reasons for building the city of Baghdad, most importantly security reasons. Therefore, this city received great attention from its builder, Caliph Al-Mansur (136-158 AH / 753-774 AD). This interest was represented in increasing its fortifications, including doors, walls, and trenches that were secured for the Abbasid Caliph Al-Mansur and his family. A great deal of security, and this interest in defensive fortifications and military organizations continued due to internal strife and revolutions and the appearance and despite the difficulties and disasters it went through, this city with its various landmarks remained a focus of admiration and interest for everyone who saw it